1979
DOI: 10.1103/physrevc.19.1276
|View full text |Cite
|
Sign up to set email alerts
|

Ga71andGa

Abstract: A study of the (t,p) reaction on the two stable Ga isotopes has been performed. The reaction protons were analyzed in a quadrupole-dipole-dipole-dipole spectrometer with a resulting energy resolution approximately 18 keV. Levels up to about 3 MeV excitation energy in "Ga and 2.75 MeV in "Ga were measured with 11 new levels observed in the first case and 18 in the second. The angular distributions have been compared to pure distributions observed in the "'"Ge(t, p) reactions at the same energy and found to corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…A combination of the results from previous experiments opens the possibility of a 1/2 − , 3/2 − ground-state doublet in 73 Ga. The existence of such a doublet is compatible with the available transfer reaction data as the population of the yrast 1/2 − state is weak compared to the 3/2 − ground state in similar experiments studying 69,71 Ga [4,6,7]. From the energy systematics, there seems to be a more general structural difference between the odd-A gallium isotopes up to 69 Ga 38 and those with 40 neutrons or more (see Fig.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…A combination of the results from previous experiments opens the possibility of a 1/2 − , 3/2 − ground-state doublet in 73 Ga. The existence of such a doublet is compatible with the available transfer reaction data as the population of the yrast 1/2 − state is weak compared to the 3/2 − ground state in similar experiments studying 69,71 Ga [4,6,7]. From the energy systematics, there seems to be a more general structural difference between the odd-A gallium isotopes up to 69 Ga 38 and those with 40 neutrons or more (see Fig.…”
Section: Introductionsupporting
confidence: 85%
“…transfer reaction 71 Ga 40 (t,p) 73 Ga 42 indicated indeed a similar shift of the L = 0 strength as it is almost equally divided over three 3/2 − states at energies of 0, 219, and 915 keV [6]. Recently, a collinear laser spectroscopy measurement confirmed the assumption of a 3/2 − ground state in all odd-A gallium isotopes, except for 73 Ga 42 and 81 Ga 50 , where the spin and parity of the ground states were found to be 1/2 − and 5/2 − , respectively [12].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…and be quasidegenerate with a 3=2 À level at less than 1 keV excitation energy. This 3=2 À state was seen previously in a (t, p) reaction study [19], where it was assigned to be the g.s.. Because of the slow release of Ga from the ion source [23] and the accumulation time in the cooler, the half-life of this 3=2 À state would have to be >200 ms to be observed in our study, assuming equal production with the 1=2 À state. This upper limit on the isomeric lifetime allows putting a lower limit of 75 eV on the 3=2 À isomeric excitation energy, by assuming a similar BðM1; 3=2 !…”
supporting
confidence: 73%
“…A nuclear spin of I ¼ 3=2 was assigned to the g.s. by Vergnes et al [19], but the observed hfs is incompatible with such a spin. A second measurement, on the 403.4 nm 2 P 1=2 !…”
mentioning
confidence: 58%